Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
y=6x (1)
y=5x-7 (2)
Substitute y into (2)
(6x)=5x-7 -- subtract 5x from both sides
x=-7
Sub x into 1
y=6(-7)
y=-42
x=-7
y=-42
y=5x-7 (2)
Substitute y into (2)
(6x)=5x-7 -- subtract 5x from both sides
x=-7
Sub x into 1
y=6(-7)
y=-42
x=-7
y=-42
First substitute 'y' in 2nd equation by right side of 1st one and you get:
[tex]Y=6x[/tex]
[tex]6x=5x+7[/tex]
now substract 5x from both sides of 2nd equal and you get:
[tex]6x-5x=5x+7-5x[/tex]
as a result of the equal above you get:
[tex]x=7[/tex]
now substitute x in very first equation by the result from above (x=7):
[tex]Y=6*7=42[/tex]
[tex]x=7[/tex]
[tex]Y=6x[/tex]
[tex]6x=5x+7[/tex]
now substract 5x from both sides of 2nd equal and you get:
[tex]6x-5x=5x+7-5x[/tex]
as a result of the equal above you get:
[tex]x=7[/tex]
now substitute x in very first equation by the result from above (x=7):
[tex]Y=6*7=42[/tex]
[tex]x=7[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.